2018
DOI: 10.1080/2162402x.2018.1503913
|View full text |Cite
|
Sign up to set email alerts
|

NEAT1 paraspeckle promotes human hepatocellular carcinoma progression by strengthening IL-6/STAT3 signaling

Abstract: The formation of paraspeckle, a stress-induced nuclear body, increases in response to viral infection or proinflammatory stimuli. Paraspeckle consists of lncRNA (nuclear paraspeckle assembly transcript 1, NEAT1) and protein components including NONO, SFPQ, PSPC1, etc., which are shown to be involved in viral infection and cancer. Both NEAT1 and NONO expression increase in human hepatocellular carcinoma (HCC) samples according to TCGA data. However, the role of paraspeckle in HCC progression needs further ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 58 publications
4
37
0
Order By: Relevance
“…Mechanistically, upregulation of NEAT1 in GSCs under ADV infection could be attributed to TLR9 activation, and knockdown of NEAT1 was accompanied by an inhibition of STAT3 expression and phosphorylation. This is consistent with several reports showing that NEAT1 promotes cancer progression by enhancing STAT3 signaling [48][49][50] .…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Mechanistically, upregulation of NEAT1 in GSCs under ADV infection could be attributed to TLR9 activation, and knockdown of NEAT1 was accompanied by an inhibition of STAT3 expression and phosphorylation. This is consistent with several reports showing that NEAT1 promotes cancer progression by enhancing STAT3 signaling [48][49][50] .…”
Section: Discussionsupporting
confidence: 94%
“…These results, in combination with literatures, suggested that NEAT1 is downstream to TLR9-MYD88 and regulates STAT3 46,[48][49][50] .…”
Section: Neat1 Is Associated With Activation Of Tlr-stat Pathway In Gsupporting
confidence: 81%
“…Accelerated loss of white adipose tissue is a salient characteristic of cachexia. IL-6 signaling through STAT3 has been shown to control this process, as evidenced by inhibition of white adipose tissue lipolysis in mice treated with anti-IL-6R antibody (Babaei et al, 2018;Wang et al, 2018a). Additionally, STAT3 is thought to be involved in cachexia-related adipose tissue breakdown by modulating enzymes involved in lipolysis.…”
Section: F Janus Kinase/signal Transducer and Activator Of Transcripmentioning
confidence: 99%
“…In HCC, lncRNA‐ATB, a mediator of transforming growth factor‐β signaling, could predispose HCC patients to metastases and could serve as a potential target for antimetastatic therapies . NEAT1 paraspeckle promotes human HCC progression by strengthening interleukin‐6/signal transducer and activator of transcription 3 signaling . DSCR8 activates the Wnt/β‐catenin pathway to promote HCC progression by the DSCR8/microRNA (miR)‐485‐5p/FZD7 axis .…”
Section: Introductionmentioning
confidence: 99%
“…8 NEAT1 paraspeckle promotes human HCC progression by strengthening interleukin-6/signal transducer and activator of transcription 3 signaling. 9 DSCR8 activates the Wnt/β-catenin pathway to promote HCC progression by the DSCR8/microRNA (miR)-485-5p/FZD7 axis. 10 The findings provide promising and valuable strategies for targeted therapy of HCC.…”
Section: Introductionmentioning
confidence: 99%